Nurse personal robot: An automated robust control nurse following robot with self leveling platform, special wheel and sensor integration for crowded hospital ward - Bukhari, Ilias; Ramachandran, Nagarajan, Prof. Dr.; Abdul Hamid, Adom, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Khaled, Helmi, Dr.; Azrul, Ahmad; Sulaiman, Bakri (Universiti Malaysia Perlis (UniMAP), 2012)
Ekspo Rekacipta dan Pameran Penyelidikan UniMAP 2012 talh dianjurkan oleh Universiti Malaysia Perlis (UniMAP) pada 11 Januari 2012 di Kampus Alam, Pauh Putra, Perlis.